Molecular Diagnosis Is Vital to the Accurate Classification and Management of Thrombotic Thrombocytopenic Purpura in Children - Karsenty, Cecile L.; Kirk, Susan E.; Helber, Hannah L.; Esquilin, Jose M.; Despotovic, Jenny M.; Grimes, Amanda B. (Frontiers in Immunology, 2022)
Thrombotic thrombocytopenic purpura (TTP) is a rare but potentially life-threatening hematologic disease, presenting a myriad of diagnostic and management challenges in children. We present 2 cases of TTP occurring in adolescents, both of which demonstrate the need for early confirmation of ADAMTS13 enzyme deficiency, presence or absence of ADAMTS13 inhibitor, and ultimately molecular testing to definitively diagnose and provide appropriate management for both congenital and acquired immune-mediated TTP.